2014
DOI: 10.5296/iss.v2i2.6402
|View full text |Cite
|
Sign up to set email alerts
|

Trailer Parks as Hotbeds of Crime: Fact or Fiction?

Abstract: Studies of how physical environments contribute to crime are both numerous and revered. Relative to these studies is the perception that subsidized public housing (housing reserved for low income residents) has been viewed as being disproportionately criminogenic. Researchers, however, have historically ignored other housing types frequented by low income residents, but not normally subsidized through public programs. This research examined crime frequencies and patterns in both subsidized public housing units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…there were also notable racial differences as whites and Latinos were much more likely to move into a mobile home compared to Blacks or Asians. Whereas prior work suggests that mobile homes differ in particular ways from other types of housing with specific consequences for neighborhoods characteristics such as crime levels (Barthe, Leone, and Stitt 2014;McCarty and Hepworth 2013), the results of this study highlight that mobile homes can play an important role in how neighborhoods change, as well. Thus, the housing stock of a neighborhood may well have long-term consequences for how the neighborhood changes.…”
Section: Resultscontrasting
confidence: 77%
“…there were also notable racial differences as whites and Latinos were much more likely to move into a mobile home compared to Blacks or Asians. Whereas prior work suggests that mobile homes differ in particular ways from other types of housing with specific consequences for neighborhoods characteristics such as crime levels (Barthe, Leone, and Stitt 2014;McCarty and Hepworth 2013), the results of this study highlight that mobile homes can play an important role in how neighborhoods change, as well. Thus, the housing stock of a neighborhood may well have long-term consequences for how the neighborhood changes.…”
Section: Resultscontrasting
confidence: 77%
“…Street robberies are more likely to be suppressed in locations in which there are more “eyes on the street.” For example, mobile home parks are often characterized by relatively high density due to the closeness of units, as well as a tendency for outdoor activity given the relatively small interior space (Barthe, Leone, & Stitt, 2014; McCarty & Hepworth, 2013). A consequence may be considerable eyes on the street, which would reduce the possibility of robberies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Qualitative and quantitative studies of trailer park stereotypes have explored the subject from both the trailer house owner's perspective and the general public's perspective. All the studies reviewed suggest these attitudes exist (Bali and Davis 2008;Barthe, Leone, and Stitt 2014;Center 2015;Consumer Financial Protection Bureau 2014;Edwards, Klemmack, and Hatos Jr. 1973;Harry 2006;Hill 1999;MacTavish 2007;MacTavish, Notter, and Shamah 2008). This paper seeks to quantify the relationship between housing choice and how that choice is viewed by society.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…For example, a 1996 study found that the average manufactured home buyer was between 40 and 49 and was a white-collar professional (Harry 2006). Another study by Barthe, Leone, and Stitt (2014) concluded that those living in a trailer park do not create significant crime problems. The authors contend that trailer home owners live near one another and feel the need to maintain the peace as their housing options are limited, especially considering the insecurity that comes with trailer park residency (Aman and Yarnal 2010).…”
Section: Affordable Housing and Trailer Park Stereotypesmentioning
confidence: 99%